2017
DOI: 10.1097/brs.0000000000002049
|View full text |Cite
|
Sign up to set email alerts
|

A Whole Exome Study Identifies Novel Candidate Genes for Vertebral Bone Marrow Signal Changes (Modic Changes)

Abstract: Study Design. Family-based study Objective. To identify rare genetic factors predisposing to Modic changes (MC).Summary of Background Data. Lumbar disc degeneration (LDD) is one of the contributing factors behind low back pain (LBP). Lumbar MC visualized as bone marrow signal intensity changes on magnetic resonance imaging (MRI) represent a specific phenotype of LDD, which has stronger association with LBP than LDD without MC.Methods. The study set consisted of two Finnish families: Family I included seven aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 51 publications
0
6
0
1
Order By: Relevance
“…For the past 20 years, the spine field has seen a surge in studies addressing human genetics and the ability to identify millions of individual single nucleotide polymorphisms in relation to various imaging and/or clinical phenotypes. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] In fact, we have been witnesses to the rise of transcriptomics, proteomics, microbiome, metabolomics and a plethora of other big data "omics" platforms along with their applications toward spine disease. Even the phenotyping of disc cells and other spinal structures, the exponential rise of molecular and biomarker epidemiology, and motion kinematic and analyses further lend to multidimensional big data considerations and integration between different disciplines.…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…For the past 20 years, the spine field has seen a surge in studies addressing human genetics and the ability to identify millions of individual single nucleotide polymorphisms in relation to various imaging and/or clinical phenotypes. [36][37][38][39][40][41][42][43][44][45][46][47][48][49] In fact, we have been witnesses to the rise of transcriptomics, proteomics, microbiome, metabolomics and a plethora of other big data "omics" platforms along with their applications toward spine disease. Even the phenotyping of disc cells and other spinal structures, the exponential rise of molecular and biomarker epidemiology, and motion kinematic and analyses further lend to multidimensional big data considerations and integration between different disciplines.…”
Section: Applications Of Deep Learningmentioning
confidence: 99%
“…This is not unexpected in the light of the Finnish population history of local isolates and enrichment of rare, functional alleles [ 16 – 18 ]. We have previously shown that specific variants associate with vertebral endplate signal changes (modic changes) in two Finnish families [ 45 ]. Functional evidence is needed, however, to understand the biological effect of the identified variants.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers believe that these processes are closely interrelated with each other and that each might play a role in the chain of events leading to MC [13,14]. Recently, novel candidate genes have also been identified as a predisposing factor [15].…”
Section: Introductionmentioning
confidence: 99%